Spirituality and Religiosity—Do They Always Go Hand in Hand? The Role of Spiritual Transcendence in Predicting Centrality of Religiosity - Dominik Borawski; Katarzyna Lipska; Tomasz Wajs (Religions)
Although spirituality and religiosity are related, they are not identical phenomena. Based on the results of previous research, we hypothesized that, of the two dimensions of spirituality—transcendence proper (TP) and spiritual openness (SO)—only the former would be a significant positive predictor of religiosity operationalized as centrality of religiosity (COR). This study included 343 participants aged 18 to 82 years (M = 32.18, SD = 10.84), who completed Scale of Spiritual Transcendence and Centrality of Religiosity Scale questionnaires. Structural equation modeling revealed that, when TP and SO were controlled for simultaneously, both predictors were significant. However, while the associations of TP with COR were strong and positive, SO turned out to be a significant but negative predictor of each aspect of COR. This suggests that spirituality can encompass elements that are negatively associated with traditional religiosity and supports the thesis that spirituality is a broader construct than religiosity.